The last days of Marilyn Monroe [compact disc, unabridged] - Patterson, James, 1947-; Edwards-Jones, Imogen (Blackstone, 2025)
"In life, Marilyn Monroe's superstardom defies classification. In death, she remains shrouded in mystery. In the months before her death, Marilyn polishes the script for her ultimately unfinished film, Something's Got to Give. In the weeks before her death, she drinks champagne on Santa Monica Beach with the last photographer to take her picture. In the days before her death, she's a guest of Frank Sinatra in the Celebrity Room at the Cal Neva Lodge. In the hours before her death, she argues with US Attorney General Bobby Kennedy and his brother-in-law Peter Lawford. In an emergency session with her psychiatrist, she confesses: 'Here I am, the most beautiful woman in the world, and I do not have a date for Saturday night.' On June 1, 2026, the world celebrates Marilyn Monroe's one hundredth birthday ... without her."--|cProvided by publisher.